Antioxidative and Metabolic Effects of Lactobacillus plantarum, Inulin, and Their Synbiotic on the Hypothalamus and Serum of Healthy Rats. (June 2020) - Hosseinifard, Elaheh-Sadat; Bavafa-Valenlia, Khadijeh; Saghafi-Asl, Maryam; Morshedi, Mohammad
Nowadays, much attention has been paid to the link between gut microbiota and brain. The beneficial metabolic effects of probiotics and prebiotics in several diseases such as diabetes and obesity have been reported. However, studies bridging the association of gut microbiome with brain function in healthy states are rare. Therefore, it was hypothesized that the administration of Lactobacillus plantarum ( L plantarum ) and inulin may affect serum and hypothalamic metabolic parameters as well as oxidative markers in healthy male rats. Daily L plantarum (10 7 CFU/mL) and inulin (5% of daily food weight) or their combination (synbiotic) was given to healthy rats. Then, serum and hypothalamic levels of leptin, insulin, and oxidative markers were measured. Administration of synbiotic for 8 weeks led to significant changes in serum levels of high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, very low-density lipoprotein cholesterol, low-density lipoprotein/high-density lipoprotein ratio, triglyceride, and total cholesterol. The intake of synbiotic also resulted in a significantly reduced hypothalamic level of malondialdehyde and increased hypothalamic superoxide dismutase (SOD). Also, L plantarum could significantly increase hypothalamic SOD level. Furthermore, synbiotic administration insignificantly increased the hypothalamic and serum levels of insulin and leptin. These findings suggest that the synbiotic could significantly improve oxidative markers and lipid profile in healthy rats. Therefore, simultaneous intake of L plantarum and inulin appears to be more effective in the amelioration of metabolic and oxidative parameters.